Peran Orang Tua dan Dukungan Keluarga dalam Keberhasilan Pendidikan Anak Disabilitas - Eldiva, Fiyola Triana; Annisa, Ridha; Fitra, Ringgi Rahmat; Jofipasi, Rendy Amora (Universitas Lancang Kuning, 2025)
This study explores the crucial role of parents and family support in the educational success of children with disabilities in Padang, Indonesia. Employing a qualitative approach with a descriptive case study involving 15 families, findings reveal that active parental involvement as educators, advocates, and case managers significantly contributes to children's academic achievement and socio-emotional development. Strong emotional support from the family fosters children's self-confidence and resilience, while financial support and extensive social networks broaden access to services. Family flexibility and adaptability are also crucial in navigating challenges. The results underscore the importance of family-centered approaches and inter-stakeholder collaboration to create an inclusive educational ecosystem that empowers children with disabilities.